The global production frontier of universities - Thomas Bolli (ETH Zurich, KOF Swiss Economic Institute, 2011)
This paper provides first micro-level evidence of the global university production frontier, allowing to estimate technical efficiencies of 273 top research universities across 29 countries between 2007 and 2009. Exploiting comparable international data improves the estimation of the production technology, allows to assess the distance of individual countries to the global frontier and enables comparison of university efficiencies between and across countries. The estimated input distance function uses undergraduate students, graduate students and citations to capture university outputs and staff to measure inputs. Contrasting two alternative econometric strategies to identify technical efficiency yields relatively stable results. Furthermore, the paper addresses the problem of unobserved heterogeneity by relating the obtained efficiency rankings to quality rankings and by exploiting the panel structure of the data to account for unobserved heterogeneity explicitly. The results suggest that technical efficiency rankings can be obtained in a relatively simple econometric setting.
Keywords: D20; I20; 330; University; Global Frontier; Efficiency; Stochastic Frontier; Unobserved Heterogeneity; True Random Effects Stochastic Frontier; Hochschulforschung; Technische Effizienz; Produktionsfunktion; Schätzung; Welt